Loin and fat quality of Portuguese local Alentejano and Bísaro pigs and their crosses - Martins, J.M. (2022)
Alentejano (AL) and Bísaro (BI) Portuguese local pig breeds cohabited in Ribatejo region for some time. Their crosses (RI pigs) and the products obtained, although appreciated, disappeared in the 1950’s without being scientifically evaluated. To assess the meat quality of RI pigs, castrated males from AL, BI, ALxBI and BIxAL genotypes were studied within the framework of the TREASURE project. Raised in a traditional outdoor system and fed commercial diets ad libitum, pigs were slaughtered at ~65 (Trial 1) and ~150 kg live weight (LW) (Trial 2), and Longissimus lumborum (LL) and dorsal subcutaneous fat (DSF) physical-chemical traits were analysed. When compared to BI, AL pigs presented LL with lower moisture (trial 1 - 73.1 vs 74.7; trial 2 - 71.0 vs 72.1 g/100g; P<0.05), and higher IMF (trial 1 - 6.7 vs 5.5; trial 2 - 6.9 vs 6.0 g/100g; P<0.05) content. LL samples from AL also had higher myoglobin (trial 1 - 0.76 vs 0.54, P<0.007; trial 2 - 0.86 vs 0.45 mg/g, P<0.05) and lower total collagen (trial 1 - 13.9 vs 17.1, P<0.05; trial 2 - 13.1 vs 16.7 mg/g DM, P<0.01) content. As to RI pigs, compared to the pure genotypes, they presented intermediate values of protein, IMF and total collagen. However, LL content of moisture, total pigments and tenderness were similar to the ones from AL. When compared to BI, LL of AL pigs presented similar proportions of saturated (SFA) (trial 1 - 35.8 vs 36.8, P=0.126; trial 2 - 34.2 vs 35.8 g/100g, P=0.094), higher proportions of monounsaturated (MUFA) (trial 1 - 48.0 vs 40.2, P<0.001; trial 2 - 48.4 vs 43.1 g/100g, P<0.05), and lower proportions of polyunsaturated fatty acids (PUFA) (trial 1 - 16.2 vs 23.0, P<0.001; trial 2 - 17.4 vs 21.1 g/100g, NS). RI pigs presented intermediate proportions of FA between the fatter (AL) and the leaner (BI) genotypes. Results from RI pigs, when compared to those form AL suggest their potential for the production of loins with identical rich colour and tenderness, and with intermediate FA profiles between AL and BI genotypes. As to DSF, when compared to BI pigs, AL presented lower moisture (trial 1 - 7.3 vs 11.0, P<0.0001; trial 2 - 5.1 vs 5.8 g/100g, NS) and higher total lipids content (trial 1 - 85.0 vs 71.5, P<0.0001; trial 2 - 88.9 vs 83.7 g/100g, P<0.05). As to the FA proportions, DSF from AL presented similar proportions of SFA (trial 1 - 38.8 vs 40.2; trial 2 - 39.8 vs 41.1 g/100g; NS), higher proportions of MUFA (trial 1 – 49.0 vs 44.3, P<0.0001; trial 2 – 49.9 vs 46.2 g/100g, P<0.002), and lower proportions of PUFA (trial 1 – 12.2 vs 15.6; trial 2 – 10.4 vs 12.7 g/100g; P<0.001). Again, RI pigs presented intermediate proportions of FA between AL and BI genotypes. In both tissues, oleic acid (C18:1 n9) was the most abundant FA on all genotypes, followed by palmitic acid (C16:0). RI pigs could therefore be an alternative to the use of other breeds on commercial crosses with the pure genotypes when pure breed production is not economically beneficial.